Desenvolvimento de têxteis técnicos para reforço de compósitos poliméricos - Lima, José Henrique Batista (2012)
Materials denominated technical textiles can be defined as structures designed and developed with function to fulfill specific functional requirements of various industrial sectors as are the cases of the automotive and aerospace industries. In this aspect the technical textiles are distinguished from conventional textile materials, in which the aesthetic and of comfort needs are of primordial importance. Based on these considerations, the subject of this dissertation was established having as its main focus the study of development of textile structures from aramid and glass fibers and acting in order to develop the manufacture of composite materials that combine properties of two different structures, manufactured in an identical operation, where each structure contributes to improving the properties of the resulting composite material. Therefore were created in laboratory scale, textile structures with low weight and different composition: aramid (100%), glass (100%) and aramid /glass (65/35%), in order to use them as a reinforcing element in composite materials with polyester matrix. These composites were tested in tension and its fracture surface, evaluated by MEV. Based on the analysis of mechanical properties of the developed composites, the efficiency of the structures prepared as reinforcing element were testified by reason of that the resistance values of the composites are far superior to the polyester matrix. It was also observed that hybridization in tissue structure was efficient, since the best results obtained were for hybrid composites, where strength to the rupture was similar to the steel 1020, reaching values on the order of 340 MPa